ANALISIS SEMIOTIKA TIPOGRAFI PADA KEMASAN KONDOM DUREX INVISIBLE: VISIBLE ATAU INVISIBLE (?) - RIhi, Samuel (JURNAL Dasarrupa: Desain dan Seni Rupa, 2024)
This text seeks to explore the complexities of typography and its intersections with gender and sexuality as seen in the typography on the packaging of Durex INVISIBLE condoms, using several semiotic typography analysis features offered by Theo van Leeuwen. The curvature feature distinguishes the use of rounded and angular shapes at every character corner, which symbolically represent masculinity and femininity, and illustrate the sexual pleasure that can be experienced by both women and men. The rounded text on the word "INVISIBLE" highlights the condom's advantage as an extremely thin and sensitive product, creating a perception of softness, gentleness, and a natural experience, as if not wearing a condom at all. Meanwhile, the angular shapes on the words "Extra Thin" and "Extra Sensitive" emphasize professionalism and the use of modern technology in condom manufacturing. The orientation feature demonstrates the product's ability to attract a wider audience, while regularity emphasizes Durex's positive sex campaign and the company's efforts to change the negative stigma surrounding condoms and sexuality. On one hand, this text demonstrates the influence of capitalism in positioning itself towards the target audience through the typography used. On the other hand, through the typography on this product packaging, sex dynamically evolves, constantly mutating to challenge essentialist understandings of itself.